Performing "Sinaran by Sheila Majid":a comparative analysis styles and technique of two bassists / Mohd Fazzizul Mohd Najed - Mohd Najed, Mohd Fazzizul (2023)
The double bass and the electric bass are two separate instruments that relate harmony and rhythm, particularly when discussing jazz music. The capacity of a bassist to completely complement an ensemble can be attained by playing electric bass and applying a correct technique in a song.In this research, a qualitative method will be used and all the information will be gathered from articles, past studies, audio visual analysis, websites, journals and books.Things that will elaborate in this study are about developing, technique in Jazz music to become more specific, this study will be more focusing on a song called Sinaran by Sheila Majid and all of the information will be observed from two bassists from Malaysia which are Ahmad Syukri bin Rush (Lados) and Nurul Ashiqeen bt Johari(Iqeen).This study shows that these two bassists show different approaches even when they are playing the same song. Bass is an instrument that most world citizens think is an easy instrument but it actually needs a lot of practice for technique to lead the player to become more comfortable with the instrument. In this study, the objective and question for this research was successful and all the information was collected.